Geochemistry of lunar meteorite Yamato-82192: comparison with Yamato-791197, ALHA81005, and other lunar samples - Warren,Paul H.; Kallemeyn,Gregory W. (1987)
P(論文) We report INAA compositional data for a 171mg bulk-rock sample of lunar meteorite Yamato-82192,and for two small clasts extracted from the matrix. The two clasts were also studied petrographically, but both appear to be polymict impact melt breccias, not greatly different in composition from the bulk rock. Like two previously-studied lunar meteorites, Y-82192 is a regolith breccia from a highlands region with remarkably low contents of incompatible elements, by the standards of the small region of the central near side that was explored by the Apollo and Luna sample-return missions. Based on disparities in mg between Y-82192 and ALHA81005,and in Eu/Al and Na/Al between Y-82192 and-791197,we argue that these meteorites probably formed at three different locations, many km apart. Considering the low probability that a crater exists which is both sufficiently large and sufficiently young to account for all three meteorites, we conclude that more than one, and probably more than two, impacts were responsible for launching these samples off the Moon. It follows that at least one of these meteorites is almost certainly a product of the Moon's far side. The coincidence that all three are regolith breccias may be explained by postulating that these rocks were created out of incoherent soils by shocks associated with the same impacts that launched them off the Moon. departmental bulletin paper